2013
DOI: 10.1177/0038038513477936
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Kinship into Being: Connectedness, Donor Conception and Lesbian Parenthood

Abstract: The meaning of kinship received little sustained attention for some time in British sociology. However, we are now beginning to see a shift, and Jennifer Mason's (2008) conceptualisation of kinship affinities makes an important contribution to emerging debates. In this article I seek to add to such debates and also provide original data from the field of donor conception and lesbian motherhood, a particularly rich field in which to explore the meaning of kin. I investigate stories about becoming parents, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 34 publications
(34 reference statements)
0
63
0
3
Order By: Relevance
“…For a couple, this path to parenthood means that the partners have to decide which of them will get pregnant (first), a choice that gives the mothers different parental roles as birth mother and non-birth mother, which must be negotiated (Abelsohn, Epstein & Ross, 2013;Hayman, Wilkes, Halcomb, & Jackson, 2013;Wojnar & Katzenmeyer, 2014; see also Ryan, 2013). Donated semen could be provided through sperm banks and fertility clinics, where the donor is anonymous to the parents and the child (Chabot & Ames, 2004;Donovan & Wilson, 2008;Frith, Sawyer & Kramer, 2012;Nordqvist, 2012Nordqvist, , 2014Vanfraussen, Ponjaert-Kristoffersen & Brewaeys, 2001). Some clinics offer identify-release donors, i.e.…”
Section: Studies On Lesbian Family Life and Practicesmentioning
confidence: 99%
“…For a couple, this path to parenthood means that the partners have to decide which of them will get pregnant (first), a choice that gives the mothers different parental roles as birth mother and non-birth mother, which must be negotiated (Abelsohn, Epstein & Ross, 2013;Hayman, Wilkes, Halcomb, & Jackson, 2013;Wojnar & Katzenmeyer, 2014; see also Ryan, 2013). Donated semen could be provided through sperm banks and fertility clinics, where the donor is anonymous to the parents and the child (Chabot & Ames, 2004;Donovan & Wilson, 2008;Frith, Sawyer & Kramer, 2012;Nordqvist, 2012Nordqvist, , 2014Vanfraussen, Ponjaert-Kristoffersen & Brewaeys, 2001). Some clinics offer identify-release donors, i.e.…”
Section: Studies On Lesbian Family Life and Practicesmentioning
confidence: 99%
“…Consequently, these couples have to develop their own view on the importance of genetic ties and social connectedness with regard to parenthood. Previous research showed that lesbian couples handle these challenges by, for instance, creating a narrative about physical resemblances or by focusing on the social bond and its influence on children (Goldberg, Downing, & Sauck, 2008;Golombok, Tasker, & Murray, 1997;Jones, 2005;Nordqvist, 2010Nordqvist, , 2014Vanfraussen, Ponjaert-Kristoffersen, & Brewaeys, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Freeman et al . , Golombok , Melhuus , Nordqvist ). In comparison, as already mentioned, donors have received much less attention.…”
Section: Donating In Context and Researchmentioning
confidence: 99%